Article Review: Biological Control of Aphids Using the Natural Predator Lady Beetle (Menochilus sexmaculatus) on Chili Plants - Pramesti, Meylita Filia; Amelia, Silfina Fara; Arista, Sekar Putri; Haryanto, Azika Saputri; Soesanto, Loekas (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Chili production is frequently hampered by Aphis sp. infestations, necessitating eco-friendly biological control alternatives. Although the predator Menochilus sexmaculatus shows potential, previous researchers explicitly noted a lack of synthesized data quantifying its specific predation rates and predator-to-prey ratios. This study aims to evaluate the biocontrol efficacy of M. sexmaculatus against aphids on chili. Following PRISMA protocols, a Systematic Literature Review (SLR) used thematic analysis on articles (2017–2026) from Scopus, Google Scholar, and ScienceDirect, using keywords